Construction of an InstantPC-derivatized glycan glucose unit database: A foundation work for high-throughput and high-sensitivity glycomic analysis. (22nd December 2021) - Xie, Yongjing; Butler, Michael
Abstract: The glycosylation profile of biotherapeutic glycoproteins is a critical quality attribute that is routinely monitored to ensure desired product quality, safety and efficacy. Additionally, as one of the most prominent and complex post-translational modifications, glycosylation plays a key role in disease manifestation. Changes in glycosylation may serve as a specific and sensitive biomarker for disease diagnostics and prognostics. However, the conventional 2-aminobenzamide-based N-glycosylation analysis procedure is time-consuming and insensitive with poor reproducibility. We have evaluated an innovative streamlined 96-well-plate-based platform utilizing InstantPC label for high-throughput, high-sensitivity glycan profiling, which is user-friendly, robust and ready for automation. However, the limited availability of InstantPC-labeled glycan standards has significantly hampered the applicability and transferability of this platform for expedited glycan structural profiling. To address this challenge, we have constructed a detailed InstantPC-labeled glycan glucose unit (GU) database through analysis of human serum and a variety of other glycoproteins from various sources. Following preliminary hydrophilic interaction liquid chromatography (HILIC) with fluorescence detection separation and analysis, glycoproteins with complex glycan profiles were subjected to further fractionation by weak anion exchange HILIC and exoglycosidase sequential digestion for cross-validation of the glycan assignment. Hydrophilic interaction ultra-performance liquid chromatography coupled with electrospray ionization mass spectrometry was subsequently utilized for glycan fragmentation and accurate glycan mass confirmation. The constructed InstantPC glycan GU database is accurate and robust. It is believed that this database will enhance the application of the developed platform for high-throughput, high-sensitivity glycan profiling and that it will eventually advance glycan-based biopharmaceutical production and disease biomarker discovery.